2008
DOI: 10.1186/1475-2875-7-79
|View full text |Cite
|
Sign up to set email alerts
|

Timing of intermittent preventive treatment for malaria during pregnancy and the implications of current policy on early uptake in north-east Tanzania

Abstract: BackgroundIntermittent preventive treatment (IPTp) is efficacious in reducing the adverse outcomes associated with pregnancy-associated malaria, however uptake of the recommended two doses is low in Tanzania, and little is known of the timepoint during pregnancy at which it is delivered. This study investigated the timing of delivery of IPTp to pregnant women attending antenatal clinics (ANC), and the potential determinants of timely uptake.MethodsStructured interviews were conducted with staff and pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
65
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 23 publications
14
65
1
Order By: Relevance
“…This highlights the need to explore other variables like sociocultural, economic, political, and individual perceptions regarding IPTp in a contextual perspective. 25 Tracking progress in relation to attainment of maternal-related MDG with respect to IPTp may be a bit difficult because the framework for effective monitoring and Note: a total of 13 women were not included in analyses because the gestational age at booking was not recorded. Abbreviations: iPTp, intermittent preventive treatment; n, number; df, degrees of freedom.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to explore other variables like sociocultural, economic, political, and individual perceptions regarding IPTp in a contextual perspective. 25 Tracking progress in relation to attainment of maternal-related MDG with respect to IPTp may be a bit difficult because the framework for effective monitoring and Note: a total of 13 women were not included in analyses because the gestational age at booking was not recorded. Abbreviations: iPTp, intermittent preventive treatment; n, number; df, degrees of freedom.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with the study in Enugu where the private providers were more aware of the timing than the public providers (6). The proper timing is very important so as to have full benefits of the policy which should be at least two or three times -during pregnancy (9). Proper timing with 3 or more doses of sulphadoxine-pyrimethamine was associated with higher birth weight and lower risk of low birth weight than the standard 2 dose regimens (12).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to assess the level of provision of IPTp and understand the underlying reasons behind the level of provision in both private and public health providers, Efforts have been made to alleviate the problem of malaria in pregnancy, this include the WHO recommendation of prompt and effective management of malaria in pregnancy, chemoprophylaxis, the use of long lasting insecticide nets and indoor residential spraying (IRS) and the use of IPTp (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…The timing of first visits to ANC clinics also influences the IPTp uptake. In this regard, [16] found that even though 48% of the participants started ANC visits before the 16 th week of pregnancy, up to 86% of this lot did not receive IPTp 1 because the gestation period was below the recommended 16 weeks. Those who did not receive proper explanation of this policy requirement were discouraged and failed to turn up for subsequent appointments.…”
Section: Factors Influencing the Uptake Of Intermittent Preventive Trmentioning
confidence: 99%
“…Furthermore, IPTp uptake significantly associated with distance to ANC facilities, domestic chores and absence of health issues during pregnancy [15], as well as gravidity [16]. Hence, primigravid women were more likely to attend ANC in time for IPTp doses than multigravid women.…”
Section: Factors Influencing the Uptake Of Intermittent Preventive Trmentioning
confidence: 99%